2015
DOI: 10.1074/jbc.m115.653261
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine/Paracrine Human Growth Hormone-stimulated MicroRNA 96-182-183 Cluster Promotes Epithelial-Mesenchymal Transition and Invasion in Breast Cancer

Abstract: Background: hGH is an orthotopically expressed oncoprotein associated with mammary epithelial cell tumorigenesis. Results:The miR-96-182-183 cluster is regulated by autocrine/paracrine hGH and targets BRMS1L and GHR. Conclusion: Autocrine/paracrine hGH promotes breast cancer epithelial-mesenchymal transition and invasion via stimulating the miRNA-96-182-183 cluster. Significance: Autocrine/paracrine hGH and the miR-96-182-183 cluster might be exploited as a therapy or prognostic marker for breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 55 publications
3
68
0
Order By: Relevance
“…The identical protective effect of GH was also seen in HCT-8 colorectal cancer cells where recombinant human GH treatment protected the tumor cells against radiation in a dose-dependent manner (183). Mechanisms of chemotherapeutic resistance in cancer includes but are not limited to (i) abundant expression of a repertoire of drug efflux pumps (184,185,186,187), (ii) sequestration of drugs in melanosomes during melanogenesis (188,189), and (iii) upregulation of EMT markers (159,190,191,192,193,194), a critical mechanism of phenotype switch and chemotherapy evasion in several types of cancers(130, 131). Recently, we reported an elaborate GH-GHR dependent mechanism of drug resistance in human melanoma(130, 131), where we attenuated GHR in human melanoma cells leading to direct downregulation of specific drug efflux pumps of the ABC family leading to increased drug efficacy at a lower dose(131).…”
Section: Role Of Gh-ghr In Cancer Therapy Resistancementioning
confidence: 87%
“…The identical protective effect of GH was also seen in HCT-8 colorectal cancer cells where recombinant human GH treatment protected the tumor cells against radiation in a dose-dependent manner (183). Mechanisms of chemotherapeutic resistance in cancer includes but are not limited to (i) abundant expression of a repertoire of drug efflux pumps (184,185,186,187), (ii) sequestration of drugs in melanosomes during melanogenesis (188,189), and (iii) upregulation of EMT markers (159,190,191,192,193,194), a critical mechanism of phenotype switch and chemotherapy evasion in several types of cancers(130, 131). Recently, we reported an elaborate GH-GHR dependent mechanism of drug resistance in human melanoma(130, 131), where we attenuated GHR in human melanoma cells leading to direct downregulation of specific drug efflux pumps of the ABC family leading to increased drug efficacy at a lower dose(131).…”
Section: Role Of Gh-ghr In Cancer Therapy Resistancementioning
confidence: 87%
“…BRMS1 is a tumor suppressor (33). It has been verified that the expression of BRMS1 was regulated by miRNAs, and that it is able to inhibit the process of epithelial-mesenchymal transition and invasion in breast cancer (33). BRMS1 also regulates a network of proteins with central roles in cancer metastasis (19,34).…”
Section: Discussionmentioning
confidence: 99%
“…miR-194 was first identified as a suppressor gene in the hepatic epithelial cells of mice by inhibiting the metastasis of liver cancer cells (36). In addition, in cancer of the gut (37,38) and kidney (39), miR-194 served a similar inhibitory role.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, it was suggested that miR-194 served a role in the promotion and progression of breast cancer (9) and pancreatic ductal adenocarcinoma (40). These studies indicated that miR-194 had various target genes (31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Previous studies have demonstrated that miR-194 inhibited cell migration and invasion, which may have contributed to the anti-tumor activity of trastuzumab on HER2-overexpressing breast cancer cells (41,42).…”
Section: Discussionmentioning
confidence: 99%